Analysis of Solid Waste Generation and Composition in Malaysia TVET Campus - Mohd Rodzi, Rodzidah (International Journal of Integrated Engineering, 2019)
Recycling, composting and the conversion of waste to energy go hand-in-hand in Malaysia, which striving for sustainable waste management. In order to assess what the best alternatives are, it is important to first understand the generation and composition of municipal solid waste (MSW). The objective of this study was to determine the generation rate and composition of MSW in Malaysia TVET campus. The survey was conducted at the Industrial Training Institute, Kuala Lumpur (ITI KL). In this study, the waste composition was categorized into 6 components, in reference to the 2014 World Bank Guidelines, namely organic/food, paper, plastic, glass, metal and others. The results from this study revealed that the rate of solid waste generation at the cafeteria was 0.141kg/capita/day (9,176.00kg per year) and 0.039kg/capita/day with an estimated 7,811.00kg per year at the dining hall. The highest composition for both sampling points was organic or food waste with cafeteria generating 82.87% (20.84kg/day) and dining hall 92.53% (19.80kg/day). This study recommends three effective practices that are suitable for improving commercial solid waste management at TVET campus in Malaysia, which are composting of food waste, giving a reward/merit/penalty as enforcement and providing adequate systematically segregated recycle bins.